Nonlinear H∞ observer design for one‐sided Lipschitz discrete‐time singular systems with time‐varying delay. (19th October 2018) - Yang, Yuxia; Lin, Chong; Chen, Bing
Summary: This paper investigates the H ∞ observer design problem for a class of nonlinear discrete‐time singular systems with time‐varying delays and disturbance inputs. The nonlinear systems can be rectangular and the nonlinearities satisfy the one‐sided Lipschitz condition and quadratically inner‐bounded condition, which are more general than the traditional Lipschitz condition. By appropriately dealing with these two conditions and applying several important inequalities, a linear matrix inequality–based approach for the nonlinear observer design is proposed. The resulting nonlinear H ∞ observer guarantees asymptotic stability of the estimation error dynamics with a prescribed performance γ . The synthesis condition of H ∞ observer design for nonlinear discrete‐time singular systems without time delays is also presented. The design is first addressed for one‐sided Lipschitz discrete‐time singular systems. Finally, two numerical examples are given to show the effectiveness of the present approach.